Systematic Review of the Association Between Physical Fitness and Musculoskeletal Injury Risk: Part 2—Muscular Endurance and Muscular Strength. Issue 11 (November 2017) - de la Motte, Sarah J.; Gribbin, Timothy C.; Lisman, Peter; Murphy, Kaitlin; Deuster, Patricia A.
Abstract : Abstract: de la Motte, SJ, Gribbin, TC, Lisman, P, Murphy, K, and Deuster, PA. A systematic review of the association between physical fitness and musculoskeletal injury risk: part 2—muscular endurance and muscular strength. J Strength Cond Res 31(11): 3218–3234, 2017—This is a systematic review and evaluation of the current evidence on the association between both muscular endurance (ME) and muscular strength (MS) and musculoskeletal injury (MSK-I) risk in military and civilian populations. MEDLINE, EBSCO, EMBASE, and the Defense Technical Information Center were searched for original studies published from 1970 through 2015 which examined associations between physical fitness (ME and MS) and MSK-I in military or civilian populations. Methodological quality and strength of the evidence were determined following criteria adapted from previously published systematic reviews. Forty-five of 4, 229 citations met our inclusion criteria. Although results for some tests did vary by sex, taken together, our primary findings indicate there is (a) a strong evidence that poor performance in a push-up test is associated with MSK-I risk; (b) moderate evidence that poor performance in sit-up test is associated with MSK-I risk; (c) moderate evidence that isokinetic ankle and knee flexion strength, and isometric strength assessments at the back, elbow, or knee are associated with MSK-I risk; and (d) limited evidence that poor performance in a pull-up test and isotonic assessments of muscular strength are associated with MSK-I. Several measures of ME/MS are moderately or strongly associated with risk of MSK-I, but additional research is needed to identify and recommend specific assessments of ME/MS that predict MSK-I in both men and women. Future studies should also consider measures of ME and MS as a function of upper body, lower body, and core strength, and their potential association with specific, rather than general, MSK-I. Abstract : Supplemental Digital Content is Available in the Text.